ANALYSIS AND DIFFERENT INTERPRETATIONS OF THE CONCEPT OF SPIRITUALITY - Akhmedova Mekhrinigor Bahodirovna (Indonesian Journal of Innovation Studies, 2022)
The article provides general information about the concept of spirituality, and opinions on the analysis of the concept of spirituality. However, the analysis and different interpretations of the concept of spirituality are deeply analyzedand based on ideas using examples.